Method for preparing ultra-pure silicic acid
Through multiple ion exchange and acid treatment combined with high-temperature crystallization and filtration, the strong alkali, weak alkali metal ions and rare earth elements in silicic acid were successfully removed, and high-purity and stable silicic acid were prepared.
Patent Information
- Application Number
- CN202411796290.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively remove strong alkalis, weak alkali metal ions and rare earth elements in silicic acid, resulting in the preparation of inadequately pure silicic acid.
Through multiple ion exchange steps, including the use of cationic resin and anionic resin, combined with acid treatment and the addition of a phosphate complexing agent, impurity ions in silicic acid are gradually removed, and the rare earth elements are further removed by high temperature crystallization and filtration.
Effective removal of strong alkali cations such as Na, K, Ca, weak alkali cations such as Al, Fe, Mg, and rare earth elements such as Ti and Zr were achieved in silicic acid, and ultra-high purity silicic acid with a content of less than 200 ppb of each metal ions was prepared, and phosphide residue was avoided and the stability of silicic acid was improved.
Smart Images

Figure BDA0005176796810000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical industry, and in particular relates to a method for preparing ultra-high purity silicic acid. Background Art
[0002] Chemical mechanical polishing is currently the only technology that can achieve global planarization, and it plays a vital role in the chip manufacturing process. The types of polishing liquids used in chemical mechanical polishing include silicon oxide, cerium oxide, aluminum oxide, etc. Silicon oxide is widely used in polishing and is used in large quantities. The manufacturing processes for silicon oxide include the silanol method, ion exchange method, silicon powder hydrolysis method, etc. The silica sol prepared by the ion exchange method is widely used in wafer rough polishing. The ion exchange method is to replace alkali metal elements with hydrogen ions through ion exchange of silicates to obtain silicic acid, and then undergo a dehydration condensation reaction to obtain silica sol, so it is crucial to prepare qualified silicic acid.
[0003] The preparation of silicic acid adopts the method of ion exchange, and the alkali metal ions in silicate are exchanged into hydrogen ions to prepare silicic acid. For example, CN101070161B adopts water glass to pass through cationic resin first, and then passes through anionic resin to obtain silicic acid. The silicic acid prepared by this method can effectively exchange alkali metal ions, but weak base ions such as aluminum ion and iron ion are difficult to be exchanged. In order to remove weak base ions, CN112299424B discloses that water glass is exchanged with cationic resin, and then acidic buffer is added, and weak base ions are ionized, and then cationic exchange resin is exchanged again to remove weak base ions. Although this method can effectively remove weak base ions, it is difficult to remove rare earth elements such as Ti and Zr, because these elements exist in the form of oxides in silicate solution for the most part, and are insoluble in acid, and are difficult to ionize, so it is difficult to remove by ion exchange. CN1379733A and the document "Study on the Zirconium Removal Process of Combined Phosphoric Acid and Sodium Phosphate in the Preparation of Scandium Oxide" ("Mining and Metallurgical Engineering", Issue 3, 2018, 115-117, 122) proposed to precipitate rare earth elements in the form of complexes by adding phosphate-based chelating agents or phosphates, but the precipitation effect is not good, and the Zr residue is still at the ppm level. In addition, this method requires the addition of a large amount of phosphate-based chelating agents or phosphates, which will cause them to remain in the system and affect the purity. In addition, the presence of phosphides can easily cause the samples to mold, affecting their storage and use.
[0004] Therefore, it is particularly important to provide a method for effectively removing rare earth elements. Only after removing strong alkali, weak alkali metal ions and rare earth elements can ultra-high purity silicic acid be prepared. Summary of the invention
[0005] In view of the above problems, the object of the present invention is to provide a method for preparing ultra-high purity silicic acid. Compared with the prior art, the method provided by the present invention can effectively remove strong alkali, weak alkali metal ions and rare earth elements, and the content of each metal ion in the obtained ultra-high purity silicic acid is less than 200 ppb, and no phosphide will remain in the system. The method is simple and is conducive to industrial realization.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] A method for preparing ultra-high purity silicic acid comprises the following steps:
[0008] (1) mixing water and silicate uniformly to obtain a mixed solution, and performing a first ion exchange through a cationic resin;
[0009] (2) adding a pH adjuster to the product obtained in step (1) to adjust the pH to 1-2, aging, and performing a second ion exchange with a cationic resin;
[0010] (3) adding phosphoric acid and rare earth oxide dispersion to the product obtained in step (2), aging, and filtering;
[0011] (4) The product obtained in step (3) is subjected to a third ion exchange through an anion resin and then added to nitric acid.
[0012] In step (1) of the present invention, silicate is mixed and diluted with water, and ion exchange is performed through a cationic resin to remove strong base cations.
[0013] In step (2) of the present invention, acid is added to the silicic acid obtained in step (1) to ionize the weak base cations, and then the weak base cations are removed by passing through a cationic resin.
[0014] In step (3) of the present invention, phosphoric acid and rare earth oxide dispersion are added to the silicate obtained in step (2), and heated at a relatively low temperature. Heating is beneficial to increasing the thermal motion rate of phosphoric acid and rare earth oxide, thereby increasing the probability of collision and facilitating the formation of seed crystals. The presence of seed crystals allows the rare earth oxides originally contained in the silicate to be bonded to the seed crystals. However, the crystal structure formed at this time is loose and has a small particle size. The structure is easily disintegrated during stirring, and the particle size is too small to be filtered and separated. High-temperature heating is then performed to allow the seed crystals and the rare earth oxides originally contained in the silicate to crystallize. The high temperature causes the loose structure to be crystallized in one step, and the particle size becomes larger and denser. The dense large particle size is separated by filtration, so that the rare earth metal impurities are removed.
[0015] In step (4) of the present invention, the silicate obtained in step (3) is passed through an anion resin to remove impurity anions such as phosphate and chlorine by ion exchange, and the silicate is added to a nitric acid base solution. Since the silicate passed through the anion resin has a pH of 4 to 5, the silicate in this pH range is very unstable and easily gels, so the silicate is added to the nitric acid base solution to reduce the pH of the silicate and improve its stability. Moreover, by adding silicate to nitric acid, the silicate can be rapidly acidified to reach a stable pH range, thereby avoiding dehydration and condensation of silicate into silicon dioxide, thereby obtaining ultra-high purity silicate with very good stability.
[0016] Preferably, the silicate in step (1) comprises one or more of sodium silicate, potassium silicate and lithium silicate, preferably sodium silicate.
[0017] Preferably, the mass concentration of silicate in the mixed solution in step (1) is 2-7%.
[0018] Preferably, the modulus of the silicate in step (1) is 3.0 to 3.5.
[0019] Preferably, the cationic resin in step (1) is one or more of a strong acid cationic resin and a weak acid cationic resin.
[0020] Preferably, in step (1), the flow rate of ion exchange is 1 to 10 BV / h.
[0021] Preferably, the pH adjuster in step (2) includes one or more of hydrochloric acid, nitric acid, citric acid, phosphoric acid, and citric acid.
[0022] Preferably, in step (2), the cationic resin is one or more of a strong acid cationic resin and a weak acid cationic resin.
[0023] Preferably, in step (2), the flow rate of ion exchange is 1 to 10 BV / h.
[0024] Preferably, in step (3), the mass fraction of the rare earth oxide in the dispersion is 20-30%.
[0025] Preferably, in step (3), the added amount of the rare earth oxide is 20 to 2000 ppm of the silicon dioxide content in the silicate.
[0026] Preferably, in step (3), the amount of phosphoric acid added is 1 to 20 wt % of the silicon dioxide content in the silicate.
[0027] Preferably, in step (3), the rare earth oxide in the rare earth oxide dispersion comprises one or more of zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide.
[0028] Preferably, in step (3), aging is carried out by staged heating, preferably comprising two stages of heating, and more preferably comprising the following steps: the first stage heating temperature is 20-40°C, and the heating time is 1-5 hours; the second stage heating temperature is 40-60°C, and the heating time is 1-5 hours.
[0029] Preferably, in step (3), the filter element used for the filtration has a precision of 1 to 5 μm.
[0030] Preferably, in step (4), the anion resin is one or more of a strong base anion resin and a weak base anion resin.
[0031] Preferably, in step (4), the flow rate of ion exchange is 1 to 10 BV / h.
[0032] The method for preparing ultra-high purity silicate provided by the present invention removes strong base cations by cation resin exchange, removes weak base metal ions by adding acid and cation resin exchange, and removes rare earth cations by adding phosphoric acid and rare earth oxide for crystallization and filtration. The silicate prepared by the present invention has a strong base cation content of Na, K, Ca, etc. of less than 100 ppb, a weak base cation content of Al, Fe, Mg, etc. of less than 100 ppb, and a rare earth element ion content of Ti, Zr, etc. of less than 200 ppb.
[0033] The silicon dioxide in the silicate described in the present invention refers to the silicon in the silicate converted into silicon dioxide.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The method provided by the present invention can not only remove strong base cations such as Na, K, Ca, and weak base cations such as Al, Fe, and Mg, but also remove rare earth element ions such as Ti and Zr to prepare ultra-high purity silicate.
[0036] (2) By using the method provided by the present invention to directly add the prepared silicic acid into the base solution of nitric acid, the silicic acid in the unstable pH range can be quickly made acidic, thereby avoiding the generation of small silicon dioxide particles by the silicic acid and greatly improving the stability of the silicic acid. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0038] Example 1
[0039] A method for preparing ultra-high purity silicic acid comprises the following steps:
[0040] (1) Mixing water and sodium silicate with a modulus of 3.3 to prepare a 5%wt sodium silicate solution, and stirring thoroughly; passing the obtained mixed solution through a strong acid cationic resin (Lanxiao 001×7) at a flow rate of 10 BV / h for the first ion exchange;
[0041] (2) adding hydrochloric acid to the silicic acid obtained in step (1) to adjust the pH to 1.5, stirring and aging for 1 hour, and passing through a strong acid cationic resin (Lanxiao 001×7) at a flow rate of 10 BV / h for a second ion exchange;
[0042] (3) adding the silicic acid obtained in step (2) to phosphoric acid and zirconium oxide dispersion, wherein the amount of phosphoric acid added is 5wt% of the silicon dioxide content in the silicate, and the amount of zirconium oxide dispersion added is 20ppm of the silicon dioxide content in the silicate, and heating is performed in stages, with the first stage being heated at 30°C for 1h and the second stage being heated at 50°C for 1h. Stirring is maintained during the heating process, and then filtering is performed using a 3μm filter element to remove precipitated crystals;
[0043] (4) The silicate obtained in step (3) is passed through a weakly basic anion resin (Suqing D301) at a flow rate of 10 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0044] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0045] Example 2
[0046] This embodiment provides a method for preparing ultra-high purity silicic acid, comprising the following steps:
[0047] (1) Mix water and potassium silicate with a modulus of 3.0 to prepare a 2%wt potassium silicate solution, and stir thoroughly; pass the resulting mixed solution through a strong acid cationic resin (Lanxiao 001x8) at a flow rate of 5 BV / h for the first ion exchange;
[0048] (2) adding nitric acid to the silicic acid obtained in step (1) to adjust the pH to 1.0, stirring and aging for 2 hours, and passing through a strong acid cationic resin (Lanxiao 001×8) at a flow rate of 5 BV / h for a second ion exchange;
[0049] (3) adding the silicic acid obtained in step (2) to phosphoric acid and zirconium oxide and titanium oxide dispersions, wherein the amount of phosphoric acid added is 1wt% of the silicon dioxide content in the silicate, and the amount of zirconium oxide and titanium oxide dispersions added is 200ppm and 100ppm of the silicon dioxide content in the silicate, respectively. The mixture is heated in stages, with the first stage being heated at 20°C for 3h and the second stage being heated at 40°C for 3h. Stirring is maintained during the heating process, and then filtering is performed using a 1μm filter element to remove precipitated crystals.
[0050] (4) The silicate obtained in step (3) is passed through a weakly alkaline anion resin (Suqing SQD-96) at a flow rate of 5 BV / h for a third ion exchange, and the silicate is added to the nitric acid base solution.
[0051] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0052] Example 3
[0053] This embodiment provides a method for preparing ultra-high purity silicic acid, comprising the following steps:
[0054] (1) Mixing water and lithium silicate with a modulus of 3.5 to prepare a 7%wt lithium silicate solution, and stirring thoroughly; passing the obtained mixed solution through a weak acid cationic resin (Suqing 112) at a flow rate of 1 BV / h for the first ion exchange;
[0055] (2) adding citric acid to the silicate obtained in step (1) to adjust the pH to 2.0, stirring and aging for 2 hours, and passing through a weak acid cationic resin (Suqing 112) at a flow rate of 1 BV / h for a second ion exchange;
[0056] (3) adding the silicic acid obtained in step (2) to phosphoric acid and cerium oxide dispersion, wherein the amount of phosphoric acid added is 20wt% of the silicon dioxide content in the silicate, and the amount of cerium oxide dispersion added is 40ppm of the silicon dioxide content in the silicate, and heating is performed in stages, with the first stage being heated at 40°C for 5h and the second stage being heated at 60°C for 5h. Stirring is maintained during the heating process, and then filtering is performed using a 5μm filter element to remove precipitated crystals;
[0057] (4) The silicate obtained in step (3) is passed through a strong base anion resin (Suqing 201×2) at a flow rate of 1 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0058] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0059] Example 4
[0060] This embodiment provides a method for preparing ultra-high purity silicic acid, comprising the following steps:
[0061] (1) Mix water and sodium silicate with a modulus of 3.5 to prepare a 5%wt sodium silicate solution, and stir thoroughly; pass the resulting mixed solution through a weakly acidic cationic resin (Lanxiao D113) at a flow rate of 6 BV / h for the first ion exchange;
[0062] (2) adding phosphoric acid to the silicic acid obtained in step (1) to adjust the pH to 2.0, stirring and aging for 3 hours, and passing through a weak acid cationic resin (Lanxiao D113) at a flow rate of 6 BV / h for a second ion exchange;
[0063] (3) adding the silicic acid obtained in step (2) to phosphoric acid and lanthanum oxide dispersion, wherein the amount of phosphoric acid added is 15wt% of the silicon dioxide content in the silicate, and the amount of lanthanum oxide dispersion added is 120ppm of the silicon dioxide content in the silicate, and heating is carried out in stages, with the first stage being heated at 35°C for 2h and the second stage being heated at 45°C for 2h. Stirring is maintained during the heating process, and then filtering is performed using a 4μm filter element to remove precipitated crystals;
[0064] (4) The silicate obtained in step (3) is passed through a strong base anion resin (Lanxiao 202) at a flow rate of 6 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0065] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0066] Example 5
[0067] This embodiment provides a method for preparing ultra-high purity silicic acid, comprising the following steps:
[0068] (1) Mix water and sodium silicate with a modulus of 3.2 to prepare a 4%wt sodium silicate solution, and stir thoroughly; pass the resulting mixed solution through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 7 BV / h for the first ion exchange;
[0069] (2) adding hydrochloric acid to the silicic acid obtained in step (1) to adjust the pH to 1.3, stirring and aging for 2 hours, and passing through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 6 BV / h for a second ion exchange;
[0070] (3) adding the silicic acid obtained in step (2) to phosphoric acid and zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide dispersions, wherein the amount of phosphoric acid added is 10wt% of the silicon dioxide content in the silicate, and the amount of zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide dispersions added is 100ppm, 100ppm, 60ppm, and 100ppm of the silicon dioxide content in the silicate, respectively. The mixture is heated in stages, with the first stage being heated at 40°C for 1h and the second stage being heated at 45°C for 2h. Stirring is maintained during the heating process, and then filtering is performed using a 2μm filter element to remove precipitated crystals.
[0071] (4) The silicate obtained in step (3) is passed through a strong base anion resin (Lanxiao 201×7) at a flow rate of 5 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0072] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0073] Example 6
[0074] This embodiment provides a method for preparing ultra-high purity silicic acid, comprising the following steps:
[0075] (1) Mix water and sodium silicate with a modulus of 3.1 to prepare a 3%wt lithium silicate and sodium silicate solution, and stir thoroughly; pass the resulting mixed solution through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 3 BV / h for the first ion exchange;
[0076] (2) adding nitric acid to the silicic acid obtained in step (1) to adjust the pH to 1.5, stirring and aging for 1 hour, and passing through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 5 BV / h for a second ion exchange;
[0077] (3) adding phosphoric acid and zirconium oxide and titanium oxide dispersion to the silicic acid obtained in step (2), wherein the amount of phosphoric acid added is 15% of the silicon dioxide content in the silicate, and the amount of zirconium oxide and titanium oxide dispersion added is 140 ppm and 100 ppm of the silicon dioxide content in the silicate, respectively; heating is performed in stages, with the first stage being heated at 35° C. for 2 h, and the second stage being heated at 40° C. for 2 h, with stirring maintained during the heating process, and then filtering using a 3 μm filter element to remove precipitated crystals;
[0078] (4) The silicate obtained in step (3) is passed through a strong base anion resin (Suqing 213) at a flow rate of 5 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0079] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0080] Comparative Example 1
[0081] (1) Mix water and sodium silicate with a modulus of 3.2 to prepare a 4%wt sodium silicate solution, and stir thoroughly; pass the resulting mixed solution through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 7 BV / h for the first ion exchange;
[0082] (2) adding hydrochloric acid to the silicic acid obtained in step (1) to adjust the pH to 1.3, stirring and aging for 2 hours, and passing through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 6 BV / h for a second ion exchange;
[0083] (3) The silicate obtained in step (2) is passed through a strong base anion resin (Lanxiao 201×7) at a flow rate of 5 BV / h to perform a third ion exchange, and the silicate is added to the nitric acid base solution.
[0084] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0085] Comparative Example 2
[0086] (1) Mix water and sodium silicate with a modulus of 3.2 to prepare a 4%wt sodium silicate solution, and stir thoroughly; pass the resulting mixed solution through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 7 BV / h for the first ion exchange;
[0087] (2) adding hydrochloric acid to the silicic acid obtained in step (1) to adjust the pH to 1.3, stirring and aging for 2 hours, and passing through a strong acid cationic resin (Lanxiao 001x7) at a flow rate of 6 BV / h for a second ion exchange;
[0088] (3) adding the silicic acid obtained in step (2) to phosphoric acid and zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide dispersions, wherein the amount of phosphoric acid added is 10wt% of the silicon dioxide content in the silicate, and the amount of zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide dispersions added is 100ppm, 100ppm, 60ppm, and 100ppm of the silicon dioxide content in the silicate, respectively. The mixture is heated in stages, with the first stage being heated at 40°C for 1h and the second stage being heated at 45°C for 2h. Stirring is maintained during the heating process, and then filtering is performed using a 2μm filter element to remove precipitated crystals.
[0089] (4) The silicate obtained in step (3) was passed through a strong base anion resin (Lanxiao 201×7) at a flow rate of 5 BV / h for a third ion exchange, and nitric acid was added dropwise to the silicate to adjust the pH.
[0090] The gold impurity content in the silicic acid obtained in this example is shown in Table 1.
[0091] Table 1
[0092]
[0093] From the data in Table 1, we can see the following points:
[0094] (1) From the data of Examples 1-6 and Comparative Example 1, it can be seen that the method provided by the present invention, by adding a rare earth oxide dispersion, crystallizing the rare earth elements in the solution, adding phosphoric acid, complexing them into a precipitate, and filtering and removing them, can effectively remove rare earth metal ions.
[0095] (2) It can be seen from the data of Examples 1-6 and Comparative Example 2 that by using the method provided by the present invention, adding silicate passed through an anion resin to a nitric acid base solution and adjusting the pH, the stability of silicate can be greatly improved.
[0096] In summary, the method provided by the present invention can effectively remove strong base cations, weak base cations and rare earth cations, prepare ultra-high purity silicic acid, and the stability of the silicic acid is excellent.
[0097] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing ultra-high purity silicic acid, comprising the following steps: (1) mixing water and silicate uniformly to obtain a mixed solution, and performing a first ion exchange through a cationic resin; (2) adding a pH adjuster to the product obtained in step (1) to adjust the pH to 1-2, aging, and performing a second ion exchange with a cationic resin; (3) adding phosphoric acid and rare earth oxide dispersion to the product obtained in step (2), aging, and filtering; (4) The product obtained in step (3) is subjected to a third ion exchange through an anion resin and then added to nitric acid.
2. The method according to claim 1, characterized in that The silicate in step (1) includes one or more of sodium silicate, potassium silicate and lithium silicate, preferably sodium silicate.
3. The method according to claim 1 or 2, characterized in that: The mass concentration of the silicate in the mixed solution in step (1) is 2-7%; the modulus of the silicate in step (1) is 3.0-3.
5.
4. The method according to any one of claims 1 to 3, characterized in that: The cationic resin in step (1) is one or more of a strong acid cationic resin and a weak acid cationic resin; in step (1), the flow rate of ion exchange is 1 to 10 BV / h.
5. The method according to any one of claims 1 to 4, characterized in that: In step (2), the cationic resin is one or more of a strong acid cationic resin and a weak acid cationic resin; in step (2), the flow rate of ion exchange is 1 to 10 BV / h.
6. The method according to any one of claims 1 to 5, characterized in that: In step (3), the added amount of the rare earth oxide is 20 to 2000 ppm of the silicon dioxide content in the silicate.
7. The method according to any one of claims 1 to 6, characterized in that: In step (3), the rare earth oxide of the rare earth oxide dispersion comprises one or more of zirconium oxide, titanium oxide, cerium oxide, and lanthanum oxide.
8. The method according to any one of claims 1 to 7, characterized in that: In step (3), the amount of phosphoric acid added is 1 to 20 wt % of the silicon dioxide content in the silicate.
9. The method according to any one of claims 1 to 8, characterized in that: In step (3), aging is carried out by staged heating, preferably comprising two stages of heating, and more preferably comprising the following steps: the first stage of heating is at a temperature of 20 to 40° C. and a heating time of 1 to 5 hours; the second stage of heating is at a temperature of 40 to 60° C. and a heating time of 1 to 5 hours.
10. The method according to any one of claims 1 to 9, characterized in that: In step (4), the anion resin is one or more of a strong base anion resin and a weak base anion resin; in step (4), the flow rate of the ion exchange is 1 to 10 BV / h.
Citation Information
Patent Citations
A method for preparing a highly active silica sol composed of ultrafine silica particles
CN101070161B
Method for manufacturing of silica sols
CN1379733A